Comparison of Positional Therapy to CPAP in Patients with Positional Obstructive Sleep Apnea - Permut, Irene (American Academy of Sleep Medicine, 2010)
STUDY OBJECTIVES: We hypothesized that positional therapy would be equivalent to continuous positive airway pressure (CPAP) at normalizing the apnea-hypopnea index (AHI) in patients with positional obstructive sleep apnea (OSA). METHODS: Thirty-eight patients (25 men, 49 ± 12 years of age, body mass index 31 ± 5 kg/m(2)) with positional OSA (nonsupine AHI < 5 events/h) identified on a baseline polysomnogram were studied. Patients were randomly assigned to a night with a positional device (PD) and a night on CPAP (10 ± 3 cm H(2)O). RESULTS: Positional therapy was equivalent to CPAP at normalizing the AHI to less than 5 events per hour (92% and 97%, respectively [p = 0.16]). The AHI decreased from a median of 11 events per hour (interquartile range 9-15, range 6-26) to 2 (1-4, 0-8) and 0 events per hour (0-2, 0-7) with the PD and CPAP, respectively; the difference between treatments was significant (p < 0.001). The percentage of total sleep time in the supine position decreased from 40% (23%-67%, 7%-82%) to 0% (0%-0%, 0%-27%) with the PD (p < 0.001) but was unchanged with CPAP (51% [36%-69%, 0%-100%]). The lowest SaO(2)increased with the PD and CPAP therapy, from 85% (83%-89%, 76%-93%) to 89% (86%-9%1, 78%-95%) and 89% (87%-91%, 81%-95%), respectively (p < 0.001). The total sleep time was unchanged with the PD, but decreased with CPAP, from 338 (303-374, 159-449) minutes to 334 (287-366, 194-397) and 319 (266-343, 170-386) minutes, respectively (p = 0.02). Sleep efficiency, spontaneous arousal index, and sleep architecture were unchanged with both therapies. CONCLUSION: Positional therapy is equivalent to CPAP at normalizing the AHI in patients with positional OSA, with similar effects on sleep quality and nocturnal oxygenation. CITATION: Permut I; Diaz-Abad M; Chatila W; Crocetti J; Gaughan JP; D'Alonzo GE; Krachman SL. Comparison of positional therapy to CPAP in patients with positional obstructive sleep apnea. J Clin Sleep Med 2010;6(3):238-243.